PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI KANTOR CAMAT PONDOK TINGGI KOTA SUNGAI PENUH - Deky Hamdani (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This study aims to find out and analyze how the influence of Leadership, Organizational Culture and Work Environment on Job Satisfaction of Employees at the Pondok Tinggi Sub-District Office, Sungai Full City. This research is categorized as a comparative causal research with a quantitative approach with a questionnaire as an instrument. The population in this study were all 21 civil servants. The sampling technique is by means of saturated or census sampling techniques. The sample in this study is to take the population or as many as 21 samples. The data used in this study are primary data obtained through questionnaires and secondary data obtained from related agencies and journals to support this research. Test the validity of the instrument using the Correclation Bivariate formula, while the reliability test uses Cronbach Alpha. Measuring tools proved to be valid and reliable for research instruments. Multiple regression analysis was used to test the research hypothesis. The results of the study showed that: Leadership (X1) had no significant effect on Job Satisfaction of Pondok Tinggi District Office Employees, Sungai Full City of (?) 1.105 with a significance of 0.132. Organizational Culture (X2) has a negative and not significant effect on Employee Job Satisfaction in Pondok Tinggi Sub-District Office, Sungai Full City as evidenced by a value (?) of -1.201. Work Environment (X3) has no significant effect on Job Satisfaction of Pondok Tinggi District Office Employees, Sungai Full City, this is evidenced by a value (?) of 0.066. And based on the test results of the three independent variables tested individually the most dominant in influencing Job Satisfaction of Pondok Tinggi District Office Employees, Sungai Full City is Organizational Culture (with a coefficient of -0.590). So it can be concluded that in this study Organizational Culture (X2) is partially a factor that has a significant effect on Job Satisfaction (Y).